180 Enhancing Engagement of Nursing Home Staff and Leaders in Intervention Development - Liza L. Behrens; Kalei Kowalchik; Miriam Miller; Andrea Murray; Marie Boltz; Jennifer Kraschnewski (Journal of Clinical and Translational Science, 2023)
OBJECTIVES/GOALS: Recruiting under-resourced, rural nursing home (NH) staff to clinical research has proven especially difficult during COVID-19. The goal for this study was to leverage an existing group of NH providers to seek their opinions on the development of a novel person-centered risk management intervention for residents with dementia. METHODS/STUDY POPULATION: This study used community engagement studios (CES) to connect and engage with community experts (NH staff and leaders) attending, or in close vicinity to, a NH provider conference in Denver, Colorado July 25-30, 2022. Led by an experienced moderator and an assistant moderator using a semi-structured discussion guide, two CES were completed with 14 community experts. Community experts took part in a 90-minute facilitated and recorded discussion to gain their perspectives on the DIGNITY (Decision-making in aging and dementia for autonomy) study procedures and instruments along with recommendations for how to improve the acceptability, feasibility, and likelihood of intervention success. The local IRB determined this study to not be human research. RESULTS/ANTICIPATED RESULTS: Community experts most often identified as white/Caucasian (64%) females (93%) holding jobs in NHs as direct-care nurse/nursing aide (n=5), nurse supervisor/director (n=4), other NH leadership (n=3), nursing aide union organizers (n=2), and state surveyor (n=1). The primary outcomes of the CES were suggestions that could be used to adapt the elements of the study design. Following CESs, transcripts were reviewed and summarized on a rapid feedback table. The study team made changes to five of the six intervention elements based on expert feedback. Most experts (79%) agreed that the DIGNITY intervention was acceptable, appropriate, and feasible to implement in the NH community. DISCUSSION/SIGNIFICANCE: This study highlighted the voices of NH staff and leaders that is often underrepresented in research development and provides critical information for how to adapt a novel intervention for future testing in rural NH communities. Results also support the usefulness of CES as a method to develop practical interventions in NH communities.